Cannabidiol oxidation product HU-331 is a potential anticancer cannabinoid-quinone: a narrative review - Judy Trac; J. Myles Keck; Joseph E. Deweese (BMC, 2021)
Abstract Cannabidiol and related cannabinoids are under exploration for the treatment of a number of disease states. The cannabinoid-quinone HU-331 has been studied as a potential anticancer therapeutic. Previous studies provide evidence that HU-331 displays anticancer activity without some of the known adverse events associated with traditional anticancer agents. In this brief review, we will explore the literature related to the activity of HU-331 in purified systems, cancer cell lines, and animal models. For example, HU-331 displays inhibitory activity against human topoisomerase IIα, a known anticancer drug target. Further, in multiple cell model systems, the IC50 value for HU-331 was less than 10 μM. In addition, mouse model systems demonstrate the ability of HU-331 to shrink tumors without causing cardiotoxicity. In addition, we will briefly review the activity of some key analogs and derivatives of HU-331 for various disease states. Taken together, the published studies support further exploration of HU-331 for the treatment of cancer and possibly other disease states.